PEMIKIRAN K.H. A.WAHID HASYIM TENTANG RELASI ISLAM DAN NEGARA - Asroni, Ahmad (UIN Sunan Kalijaga Yogyakarta, 2020)
This article describes the thought and political wisdom of K.H.A. Wahid Hasyim about the relationship between Islam and the state. As one of the founders of the Nation, A. Wahid Hasyim was known as a true nationalist figure. This is among others can be seen from its acceptance of the overall chest to the deletion of the Jakarta Charter and the entire formula that explicitly contains Islam in the opening and body/main text of UUD 1945. Although he was one of the people who persistently proposed Islam as the basis of the country, but in his perspective, the unity of the nation of Indonesia is much more important than formal recognition of Islam. The acceptance of Pancasila and the UUD 1945 by A. Wahid Hasyim (as well as several Islamic figures at the time) signifies that they are willing to sacrifice for the interes of the nation. Keywords: ideologization of Islam, formalization, state, nationalism